On the minimum transport required to passively suppress runaway electrons in SPARC disruptions. (1st March 2023) - Tinguely, R A; Pusztai, I; Izzo, V A; Särkimäki, K; Fülöp, T; Garnier, D T; Granetz, R S; Hoppe, M; Paz-Soldan, C; Sundström, A; Sweeney, R
Abstract: In Izzo et al (2022 Nucl. Fusion 62 096029), state-of-the-art modeling of thermal and current quench (CQ) magnetohydrodynamics (MHD) coupled with a self-consistent evolution of runaway electron (RE) generation and transport showed that a non-axisymmetric ( n  = 1) in-vessel coil could passively prevent RE beam formation during disruptions in SPARC, a compact high-field tokamak projected to achieve a fusion gain Q  > 2 in DT plasmas. However, such suppression requires finite transport of REs within magnetic islands and re-healed flux surfaces; conservatively assuming zero transport in these regions leads to an upper bound of RE current ∼ 1 M A compared to ∼ 8.7 M A of pre-disruption plasma current. Further investigation finds that core-localized electrons, within r / a < 0.3 and with kinetic energies ∼ 0.2 – 15 M e V, contribute most to the RE plateau formation. Yet only a relatively small amount of transport, i.e. a diffusion coefficient ∼ 18 m 2 s − 1, is needed in the core to fully mitigate these REs. Properly accounting for (a) the CQ electric field's effect on RE transport in islands and (b) the contribution of significant RE currents to disruption MHD may help achieve this.